Perceptions about bats and the ecosystem service of seed dispersal in the community "El Bejucal", Tabasco - Hernández Rodríguez, Sergio; López Medellín, Xavier; Jácome Flores, Miguel (Instituto de Ecología, A.C., 2024)
The existing beliefs, myths and stories in the symbolic realm of bats have a great influence on the valuation of people. The objective of this research is to know the perception that exists among the inhabitants of the El Bejucal community about bats and the ecosystem service of seed dispersal. This research was performed in two phases, first semi-structured interviews were applied to the inhabitants to learn about their perceptions, and then we gave an awareness workshop among them and with the final aim to evaluate the effectiveness of our environmental education actions and the changes in perceptions and knowledge. The interviews gathered the traditional knowledge about bats, the services they provide and their presence in the daily life of the interviewees. Our results indicate how prejudices and myths associated with bats still persist in communities, which evidences the need to implement communication and environmental education, since it is our responsibility to educate and return the people that live in the sites where we work the knowledge we are developing